Effect of obesity on the effectiveness of cardiac resynchronization to reduce the risk of first and recurrent ventricular tachyarrhythmia events. Issue 1 (December 2016) - Szepietowska, Barbara; Polonsky, Bronislava; Sherazi, Saadia; Biton, Yitschak; Kutyifa, Valentina; McNitt, Scott; Aktas, Mehmet; Moss, Arthur; Zareba, Wojciech
Abstract Background Obesity is associated with multiple adverse cardiovascular conditions and may increase the risk of ventricular tachyarrhythmias (VT/VF). There is limited data on the association between obesity and risk of VT/VF requiring appropriate implantable cardioverter-defibrillator (ICD) therapies and the effectiveness of cardiac resynchronization therapy (CRT) to reduce risk for VT/VF. The multicenter automatic defibrillator implantation trial with cardiac resynchronization therapy (MADIT-CRT) was design to investigate effectiveness of CRT therapy to reduce cardiovascular outcome for patients with heart failure (HF) and reduced ejection fraction. Methods and results We identified patients enrolled in the MADIT CRT trial as obese (n = 433) and non-obese (n = 845) and analyzed their risk for appropriate device therapy for VT/VF, repeated VT/VF events, fast VT/VF, as well as events after first VT/VF episodes. Obesity was defined as body mass index (BMI) ≥30 kg/m2 . Among ICD patients, the risk of first appropriate ICD therapy for VT/VF at 3 years was similar between obese and non-obese patients (23 vs. 21 %, p = 0.76). CRT-D treatment reduced the risk of first appropriate ICD therapy both in non-obese ([HR]; 0.58 [CI]: 0.42–0.79; p < 0.001) and obese patients (HR 0.75, 95 % CI 0.5–1.38; p = 0.179) (interaction p value 0.323). Similarly, a significant reduction in the risk of fast VT/VF was observed in non-obese patients ([HR]; 0.49 [CI]: 0.33–0.73; p < 0.001) and obese ([HR]; 0.49 [CI]: 0.29–0.81; p < 0.01), (interaction p value 0.984). Conclusion Obese and non-obese patients with mild heart failure have a similar risk of ventricular tachyarrhythmias. Obesity in mild heart failure did not diminish the clinical benefit of cardiac resynchronization therapy to reduce risk for appropriate ICD therapy. Clinical trial registration http://clinicaltrials.gov/ct2/show/NCT00180271